2022
DOI: 10.1021/acs.jafc.2c04593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorogenic Acid via Upregulating Resolvin D1 Inhibiting the NF-κB Pathway on Chronic Restraint Stress-Induced Liver Inflammation

Abstract: Chronic stress can cause chronic inflammatory injury to the liver. Chlorogenic acid (CGA) is known to have a wide range of biological activities and anti-inflammatory effects. Resolvin D1 (RvD1) is a polyunsaturated fatty acid derivative that has inhibitory effects on a variety of inflammatory diseases. However, whether CGA can inhibit liver inflammation in chronic stress through RvD1 remains unclear. In this work, male rats were subjected to restraint stress for 6 h every day and built a chronic stress model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…CGA has been shown to have anti-inflammatory, antioxidant, anti-apoptotic, and anti-viral effects. At the same time, the current study found that CGA could alleviate chronic stress-induced liver, nerve, and intestinal damage. , Tian et al found that CGA protects cardiomyocytes via inhibiting NF-κB in the mice heart failure model, and the mitogen-activated protein kinases (MAPK) also play an important role in this . There are three main types of MAPK, p38MAPK, c-Jun amino-terminal kinase (JNK), and extracellular signal-regulated kinase 1/2 (ERK1/2).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…CGA has been shown to have anti-inflammatory, antioxidant, anti-apoptotic, and anti-viral effects. At the same time, the current study found that CGA could alleviate chronic stress-induced liver, nerve, and intestinal damage. , Tian et al found that CGA protects cardiomyocytes via inhibiting NF-κB in the mice heart failure model, and the mitogen-activated protein kinases (MAPK) also play an important role in this . There are three main types of MAPK, p38MAPK, c-Jun amino-terminal kinase (JNK), and extracellular signal-regulated kinase 1/2 (ERK1/2).…”
Section: Introductionmentioning
confidence: 56%
“…At the same time, the current study found that CGA could alleviate chronic stressinduced liver, nerve, and intestinal damage. 18,19 mice heart failure model, and the mitogen-activated protein kinases (MAPK) also play an important role in this. 20 There are three main types of MAPK, p38MAPK, c-Jun amino-terminal kinase (JNK), and extracellular signal-regulated kinase 1/2 (ERK1/2).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Emulsifying activity index EAI(m 2 /g)= 2×2.303×A 0 ×100 C×0.01×(1-θ)×10 4 (2) Note: C is the sample concentration (mg/mL), θ is the volume fraction of oil phase (0.20).…”
Section: Determination Of Emulsification Characteristicsmentioning
confidence: 99%
“…Therefore, in order to improve the utilization rate of PP, it is extremely important to modify PP. Chlorogenic acid(CA) is a common polyphenol in food and diet, and is often used with protein in food processing [3,4] . Jiang [5] combined CA with whey protein and casein.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic stress is caused by long-term exposure to low-intensity stressors, which will suppress the disease resistance of animals. The liver is the major organ of metabolism, detoxification, and immunity, and it is also one of the organs most vulnerable to injury when chronic stress occurs. Stress has been reported to disrupt the hepatic immune tolerance through multiple mechanisms, leading to liver damage . Chronic stress activates the hypothalamic–pituitary–adrenal (HPA) axis and autonomic nervous system (ANS).…”
Section: Introductionmentioning
confidence: 99%